Estimation by the Analogy Principle - Manski, Charles F. (Econometrica, 1987)
The analogy principle proposes that population parameters be estimated by sample statistics which make known properties of the population hold as closely as possible in the sample. Applications of the analogy principle are ubiquitous. Nevertheless, estimation theory has not been studied from a consistent analog perspective. This paper makes a start.